2016
DOI: 10.1093/cid/ciw282
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Translation Gap: Toolkit-based Implementation of Universal Decolonization in Adult Intensive Care Units Reduces Central Line–associated Bloodstream Infections in 95 Community Hospitals

Abstract: Background. Challenges exist in implementing evidence-based strategies, reaching high compliance, and achieving desired outcomes. The rapid adoption of a publicly available toolkit featuring routine universal decolonization of intensive care unit (ICU) patients may affect catheter-related bloodstream infections.Methods. Implementation of universal decolonization-treatment of all ICU patients with chlorhexidine bathing and nasal mupirocin-used a prerelease version of a publicly available toolkit. Implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
(18 reference statements)
0
27
1
1
Order By: Relevance
“…), evaluation tool Provider : Alcohol hand rubs Patient : Leaflet, posters Other intervention : Campaign project manager trained pilot teams in evaluation tool use Uptake : NR Utility : Respondents indicated the framework for implementation was helpful and the major success element were the alcohol hand rubs Providers : 70% of nurses and 60% of doctors agreed that the presence of wipes encouraged them to clean their hands, 76–84% indicated posters made staff think about their hand hygiene, 74% indicated they cleaned their hands more frequently Procedures : Compliance with hand cleaning increased from 32% (before toolkit) to 41% at 3 months and 63% at 6 months Patients : 16/43 patients had asked staff to clean their hands, 35/43 found posters etc. usefulSeptimus 2016 [84]; Huang 2013 [91]USHospital-acquired infectionsHospital# hospitals: 136 ICUs in 95 hospitals# providers: NR# patients: 305583 admissions (pre-period)/ 102220 (post)Pre-postUniversal ICU Decolonization Toolkit: An Enhanced Protocol Implementation : Protocol overview, scientific rationale, flow chart, readiness assessment and FAQ, training and educational materials, chlorohexane bathing skills assessment Provider : Nursing protocol, safety information Patient : NR Other intervention : Five coaching calls Uptake : NR Feasibility : Challenges identified included concerns about mupirocin resistance and questions about peer review of the original trial results, Most facilities were able to easily implement daily CHG bathing, as this practice, fit within normal nursing work flow and did not require a physician order. Providers : NR Procedures : NR Patients : The raw CLABSI rate (CLABSI events divided by number of central line–day) dropped from 1.1/1000 to 0.87/1000 central line–days postintervention. There were 672 CLABSIs per 587 891 central line–days in the 24-month preintervention period, and 181 CLABSIs per 208 175 central line–days in the 8-month post-intervention period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), evaluation tool Provider : Alcohol hand rubs Patient : Leaflet, posters Other intervention : Campaign project manager trained pilot teams in evaluation tool use Uptake : NR Utility : Respondents indicated the framework for implementation was helpful and the major success element were the alcohol hand rubs Providers : 70% of nurses and 60% of doctors agreed that the presence of wipes encouraged them to clean their hands, 76–84% indicated posters made staff think about their hand hygiene, 74% indicated they cleaned their hands more frequently Procedures : Compliance with hand cleaning increased from 32% (before toolkit) to 41% at 3 months and 63% at 6 months Patients : 16/43 patients had asked staff to clean their hands, 35/43 found posters etc. usefulSeptimus 2016 [84]; Huang 2013 [91]USHospital-acquired infectionsHospital# hospitals: 136 ICUs in 95 hospitals# providers: NR# patients: 305583 admissions (pre-period)/ 102220 (post)Pre-postUniversal ICU Decolonization Toolkit: An Enhanced Protocol Implementation : Protocol overview, scientific rationale, flow chart, readiness assessment and FAQ, training and educational materials, chlorohexane bathing skills assessment Provider : Nursing protocol, safety information Patient : NR Other intervention : Five coaching calls Uptake : NR Feasibility : Challenges identified included concerns about mupirocin resistance and questions about peer review of the original trial results, Most facilities were able to easily implement daily CHG bathing, as this practice, fit within normal nursing work flow and did not require a physician order. Providers : NR Procedures : NR Patients : The raw CLABSI rate (CLABSI events divided by number of central line–day) dropped from 1.1/1000 to 0.87/1000 central line–days postintervention. There were 672 CLABSIs per 587 891 central line–days in the 24-month preintervention period, and 181 CLABSIs per 208 175 central line–days in the 8-month post-intervention period.…”
Section: Resultsmentioning
confidence: 99%
“…For feasibility, ten studies indicated that the interventions or best practices included in the toolkit were not feasible [13, 21, 25, 27, 34, 59, 73, 8486]. For example, a quarter of participants in one study reported that systematic screening for obesity was not feasible in clinical practice [21].…”
Section: Resultsmentioning
confidence: 99%
“…Investments in infection reduction have been posed in intensive care units, which has been defined as an "epicenter" of nosocomial infections, by measurements of skin decolonization involving daily chlorhexidine bathing [3]. The practice was adopted because of evidence that universal decolonization reduces device-associated bacteremia, all-cause bacteremia, and multidrug-resistant organisms [3,4]. However, the nasal carriage is also unavoidable for endogenous infections and for transmission to other individuals, as the colonization of extra nasal sites often originates from the nasal reservoir [5].…”
Section: Introductionmentioning
confidence: 99%
“…Investments in infection reduction have been posed in intensive care units, which has been de ned as an "epicenter" of nosocomial infections, by measurements of skin decolonization involving daily chlorhexidine bathing 3 . The practice was adopted because of evidence that universal decolonization reduces device-associated bacteremia, all-cause bacteremia, and multidrugresistant organisms 3,4 . However, the nasal carriage is also unavoidable for endogenous infections and for transmission to other individuals, as the colonization of extra nasal sites often originates from the nasal reservoir 5 .…”
Section: Introductionmentioning
confidence: 99%